Pengaruh Nilai Sosial, Dukungan Keluarga, dan Ekspektasi Imbalan Finansial terhadap Minat Karier Mahasiswa Akuntansi Publik: The Influence of Social Values, Family Support, and Financial Expectations on Accounting Students’ Career Interest in the Public Sector - Ghea Fauziah; Ika Sebti Nurkumalasari (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2026)
This study aims to examine how accounting students’ interest in pursuing careers in the public sector is influenced by social values, family support, and expectations of financial rewards. In order to understand how one's interests in a certain field develop, this study takes a quantitative method by drawing on the Social Cognitive Career Theory and the Theory of Planned BehaviorThe population of this study consists of all students enrolled in the Public Sector Accounting Study Program at Politeknik Negeri Madiun. The modest sample size allowed all 165 students to participate as responders. A total of 146 valid answers were used for data analysis from an online questionnaire. The data were analyzed using the PLS-SEM approach. Results show that interest in working for the government is positively and significantly impacted by social ideals, familial support, and expectations of financial return. Besides financial considerations, these findings add credence to the idea that students' social values and the support they get from their communities play a role in shaping their professional achievements.